2016
DOI: 10.1093/bja/aev367
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative supplementation with fibrinogen concentrate in cardiac surgery: A randomized controlled study

Abstract: NCT 00968045.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 18 publications
(17 reference statements)
1
38
1
Order By: Relevance
“…Fibrinogen supplementation does not always increase the serum fibrinogen level. In this regard, Jeppsson et al [20] found an even lower postoperative fibrinogen level in their treatment group. Also, 2 g of the concentrate might not be enough to increase the fibrinogen level.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Fibrinogen supplementation does not always increase the serum fibrinogen level. In this regard, Jeppsson et al [20] found an even lower postoperative fibrinogen level in their treatment group. Also, 2 g of the concentrate might not be enough to increase the fibrinogen level.…”
Section: Discussionmentioning
confidence: 83%
“…Despite previous experiences in blood loss control with fibrinogen concentrate in various surgical fields , questions about its effectiveness in prostatectomy patients still remain. Hence, this clinical trial investigated the effects and possible adverse effects of fibrinogen concentrate on the amount of bleeding in men undergoing TUR‐P.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have provided evidence supporting its superiority to conventional treatment using FFP and a recently published trial (FIBRES) demonstrated non‐inferiority of fibrinogen concentrate compared with Cryo usage in severe bleeding . Other studies have shown conflicting results . Results from single‐center studies with different designs (prophylactic approach or bleeding assessment) could not be confirmed by an international multicenter trial (REPLACE) .…”
Section: Introductionmentioning
confidence: 99%